2018
DOI: 10.1371/journal.pone.0193033
|View full text |Cite
|
Sign up to set email alerts
|

Robotic radical hysterectomy is superior to laparoscopic radical hysterectomy and open radical hysterectomy in the treatment of cervical cancer

Abstract: ObjectiveCervical cancer (CC) continues to be a global burden for women, with higher incidence and mortality rates reported annually. Many countries have witnessed a dramatic reduction in the prevalence of CC due to widely accessed robotic radical hysterectomy (RRH). This network meta-analysis aims to compare intraoperative and postoperative outcomes in way of RRH, laparoscopic radical hysterectomy (LTH) and open radical hysterectomy (ORH) in the treatment of early-stage CC.MethodsA comprehensive search of Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
(41 reference statements)
2
36
1
4
Order By: Relevance
“…There is a high prevalence (20–100 per cent) of musculoskeletal pain among surgeons which may affect multiple sites. In addition to having putative benefits for the patient, robotic‐assisted laparoscopic surgery (RALS) is thought to be less physically demanding for the surgeon than conventional laparoscopy (LAP). The greatest muscle strain may be in the neck and shoulders for LAP and the lower back in RALS, but others reported that the shoulders and forearm flexors took the strain in RALS.…”
Section: Introductionmentioning
confidence: 99%
“…There is a high prevalence (20–100 per cent) of musculoskeletal pain among surgeons which may affect multiple sites. In addition to having putative benefits for the patient, robotic‐assisted laparoscopic surgery (RALS) is thought to be less physically demanding for the surgeon than conventional laparoscopy (LAP). The greatest muscle strain may be in the neck and shoulders for LAP and the lower back in RALS, but others reported that the shoulders and forearm flexors took the strain in RALS.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous observational studies and meta-analyses report superior results in blood loss, hospital stay and complication rates compared with the laparotomic approach. [1][2][3][4] In addition, equal survival rates of robot-assisted laparoscopy and laparotomy were suggested. [5][6][7][8] However, a recent trial by Ramirez et al, 9 which randomised between minimally invasive surgery (MIS) and laparotomy, showed a significantly increased recurrence rate and reduced overall survival in patients receiving MIS for International Federation of Obstetrics and Gynecology (FIGO) stage Ia1-Ib1 cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Sert et al[13] first published the results of robotic radical hysterectomy (RRH) with lymphadenectomy. To date, there have been relatively more studies of RRH for cervical cancer in foreign countries[14-19]. Our center started to provide a service to perform RRH for cervical cancer relatively early in China, and it has also accumulated rich clinical experience.…”
Section: Introductionmentioning
confidence: 99%